OPPORTUNITIES FOR DEVELOPING SUCCESS IN EDUCATION AND EDUCATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article discusses the important aspects of achieving the quality and effectiveness of education. In the modern educational process, student activity and its success are considered the most important result, and in order to achieve the intended goal, the educational process must be effectively organized. This requires great skill and intellectual intelligence from the teacher. In this sense, this article presents proposals and recommendations regarding the success of the student in education and his role in the development of students' educational activities.